Local Wisdom vs. Public Policy: Nagari Batu Bajanjang's Rejection of Government Projects in Indonesia - Syafnil; Arifin, Zainal; Delfi, Maskota (Sapientia Humana: Jurnal Sosial Humaniora, 2023)
The Indonesian government believes that the development of an electric power plant in Gunung Talang will have a positive impact on improving the welfare of the community. However, this plan is not uniformly accepted by the local community, as their area will be affected by the development. The local community around Gunung Talang who will be affected by it have protested the government's plan. It is important to consider the local community's thoughts in development planning. The methodology used in this study is ethnography, utilizing emic and etic data, and employing purposive sampling, key informants, and ordinary informants. The results indicate that the local community's understanding and beliefs about their customary land are essential to their survival and well-being. They feel that the land is a source of life that needs to be protected and preserved. They also feel that the government has not considered their needs and interests in this development plan. The conclusion of this study is that involving the local community in development planning and considering their perspective is crucial to minimizing negative impacts and maximizing positive outcomes from it. Therefore, this can provide broader benefits to the community and strengthen social and ecological sustainability.